1994
DOI: 10.1139/e94-095
|View full text |Cite
|
Sign up to set email alerts
|

The seismic velocity and Poisson's ratio structure of the Kapuskasing uplift from laboratory measurements

Abstract: The compressional (Vp) and shear (Vs) wave velocity structure of the Kapuskasing uplift have been determined as a function of depth, propagation direction, and polarization from laboratory velocity measurements to confining pressures of 600 MPa on oriented samples from known structural levels of the complex. Based on the relative field abundances of the lithologies measured, the three principal terranes exposed in the uplift are characterized at depth by the following average valves of V , V, , and apparent Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Both the P and S wave velocities of each sample were measured at hydrostatic confining pressures up to 600 MPa using standard pulse transmission methods [ Christensen , ]. The localities, densities, and modal compositions of the 25 samples from this study, collected from metamorphic belts in Canada and China and measured using our pressure apparatus (a 7 t, double‐walled steel vessel with a 40 cm long by 10 cm diameter working chamber, which operated to a pressure up to 650 MPa [ Ji et al , ; Salisbury and Fountain , ]), are listed in Table S1 along with one or two key references about their geological settings. P waves were generated and received by lead zirconate transducers with a 1 MHz resonance frequency, while S waves were generated and received using lead zirconate‐titanate transducers.…”
Section: Measurements Of Seismic Velocitiesmentioning
confidence: 99%
“…Both the P and S wave velocities of each sample were measured at hydrostatic confining pressures up to 600 MPa using standard pulse transmission methods [ Christensen , ]. The localities, densities, and modal compositions of the 25 samples from this study, collected from metamorphic belts in Canada and China and measured using our pressure apparatus (a 7 t, double‐walled steel vessel with a 40 cm long by 10 cm diameter working chamber, which operated to a pressure up to 650 MPa [ Ji et al , ; Salisbury and Fountain , ]), are listed in Table S1 along with one or two key references about their geological settings. P waves were generated and received by lead zirconate transducers with a 1 MHz resonance frequency, while S waves were generated and received using lead zirconate‐titanate transducers.…”
Section: Measurements Of Seismic Velocitiesmentioning
confidence: 99%
“… Average values of data from Fountain and Salisbury [], Fountain et al . [], and Salisbury and Fountain [].…”
Section: Geophysical 3‐d Model Of the Regional Crustmentioning
confidence: 99%
“…The density of each upper crustal lithologic unit is obtained from the literature. Fountain et al [1990], Salisbury and Fountain [1994], and Fountain and Salisbury [1996] provide laboratory density measurements for a variety of samples from the Canadian Shield. The samples are here reclassified into tonalite-tonalite gneiss, granite-granodiorite, and greenstone belt volcanic rocks and the average and standard deviation of the density are used for these lithologic units.…”
Section: Geophysical Model Of Regional Upper Crustmentioning
confidence: 99%
“…This has been effectively demonstrated by laboratory experiments [e.g., Kern , 1982; Christensen , 1996]. Christensen [1996] recognized the difficulty of obtaining good resolution of σ based on V p and V s derived from refraction experiments, despite some studies that have shown good agreement of laboratory and refraction velocity data [e.g., Salisbury and Fountain , 1993]. Experimental data [ Kern , 1982; Christensen , 1996] show σ mainly depends on rock composition rather than on P‐T conditions [ Tarkov and Vavakin , 1982], although some studies [e.g., Christensen , 1996] have shown that increasing metamorphic grade has a significant effect and increases V p /V s .…”
Section: Introductionmentioning
confidence: 99%